PERSEPSI MAHASISWA AKUNTANSI UNIVERSITAS BUNDA MULIA TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
The career choice of a bachelor in accounting is really varied. They can become public accountant, company accountant or managerial accountant. Moreover, they can also choose to be governmental or educational accountant.  There are a lot of factors to consider in choosing a career such as financial reward, professional training, professional acknowledgement, social values, working environment, job market and personality considerations. This is a descriptive research aimed to find out the most favorable career in accounting favored by Universitas Bunda Mulia accounting major students and to acquire their perception on factors influencing career choice. This research is done using tools analyzing frequency distribution by means of calculating the value of modus and mean and quartile. Based on the results, it is known that the career choice favored by Universitas Bunda Mulia accounting major students are to become managerial and public accountant. Managerial accountant is the most favorable and public accountant is the second most favorable. The student who have choose as managerial accounting have positive perception on the existence of professional training, social values, working environment and job market consideration. The students who have choose as public accounting have positive perception on the existence of professional training, professional acknowledgment, environment work and personality consideration.  Keywords: Perception, career, public accountant, managerial accountant, educational accountant and governmental accountant.